2018
DOI: 10.3390/ma11071055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Speed on Cutting Characteristics of Cement-Based Materials

Abstract: The results of an experimental investigation on the physical and chemical characteristics of cement-based materials under laser interactions are presented. The laser cutting tests were conducted using a multi-mode continuous fiber laser with a laser power of 1 kW. The experimental variables were laser speed, water to cement ratio, and material compositions including cement paste, cement mortar, and ultra high-performance concrete (UHPC). In order to evaluate the mass removal mechanisms of cement-based material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…LU set the different weight of silica fume and silica powder, respectively. The detailed mixture design and compressive strength can be found in Lee et al [16].…”
Section: Materials and MIX Designmentioning
confidence: 99%
See 2 more Smart Citations
“…LU set the different weight of silica fume and silica powder, respectively. The detailed mixture design and compressive strength can be found in Lee et al [16].…”
Section: Materials and MIX Designmentioning
confidence: 99%
“…MRZ is the area where the material is vaporized and removed by laser. On the contrary, HAZ is the area where material is not removed and only affected by heat [16,17]. Since the perfectly cut specimens exist only in the MRZ at the cut surface, the partially penetrated specimen is used to compare MRZ with HAZ.…”
Section: Microstructure Of the Processed Cement-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research demonstrated the feasibility of remotely using a laser-based concrete cutting technique by specifying the core diameter of the fiber and the fiber length as parameters. Lee et al [13] used a 1 kW multimode continuous fiber laser (YLS-1000 MM, IPG) emitting at 1070 nm to evaluate the variation of physical and chemical composition of cement-based materials after the laser cutting performance. In particular, they measured compositional variations using energy-dispersive X-ray spectroscopy to study the compositional change before and after the laser interaction with cement-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Laser machining can be performed on various materials without tool wear and additional cost. The method is non-contact processing, which provides flexibility in processing [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Among the laser system used by industries, the CO 2 laser has more economical than other laser systems.…”
Section: Introductionmentioning
confidence: 99%